A disclosure of social and environmental results/economy resulting from the implementation of reverse logistics and final disposal of the post‐consumption product: The case of computer peripherals industry. Issue 3 (23rd April 2018) - Slomski, Valmor; Slomski, Vilma Geni; Valim, Gilson Giungi; Vasconcelos, Ana Lúcia Fontes de Souza
Abstract: This research was conducted with the objective of determining and evidencing the social and environmental/economic results from the implementation of a reverse logistics program providing for the recycling, reuse, and, when necessary, final, environmentally correct disposal of post‐consumption products and product wastes by a multinational manufacturer of computer peripherals with an operation based in the city of São Paulo, Brazil. The reverse logistics process ( logisticareversa, or, in this paper, LR) was intended to meet the objectives and principles of the regulatory framework defined in the National Solid Waste Policy (PNRS) in Brazil. A single case study was carried out. The results showed that after the adoption of the solid waste management policy, the study company no longer disposed of 1, 413, 552 kilograms (kg) of materials classified as mixed iron, polystyrene, cardboard, toner powder, and plastic in landfills. The LR process made a profit in two companies: the company surveyed made, in Brazilian reais (R), R$ 9, 188, 185.51, and the company contracted to carry out the process made, R$ 411, 325.97. This latter profit is called by us the "social profit." The measurement of the environmental/economic, social, and financial results by internalizing the expenses of the LR program into the costs of production shows that reuse and recycling better meets the needs of society and the company than landfilling these post‐consumption materials. Furthermore, the use of cost accounting allows the verification of other goals not indicated in the current model, such as the generation of employment, income, mitigation of environmental problems, and the profit earned by the company contracted to implement the LR process. We also conclude that cost accounting makes it possible to obtain necessary information for decision makers, who are seeking to neutralize environmental impacts and promote sustainable development, thus harmonizing the economic, social, and environmental aspects, to understand the impacts of the LR process.